Minat Generasi Muda Keluarga Petani terhadap Sektor Pertanian di Desa Karangligar, Kecamatan Telukjambe Barat, Kabupaten Karawang - Julia, Anna; Heryanto, Mahra Arari; Utami, Hesty Nurul; Rachmawati, Erna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The current phenomenon of aging farmers continues to occur and has resulted in a crisis of young farmers. It is hoped that through their experiences, farmers' children can become young people who can continue the agricultural sector in the future. This research aimed to analyze (1) the interest of farmer's children in Karangligar Village towards the agricultural sector and (2) the relationship between the interests of farmer's children and the factors influencing interest in the agricultural sector. This research used a descriptive quantitative approach with scoring methods and Spearman rank correlation. A sample of 80 farmer's children aged 16 – 30 years was taken using the Slovin formula and proportional stratified sampling technique. The research results indicate that there is interest from the younger generation of farming families in Karangligar Village, accompanied by low participation and curiosity about agriculture, so policy development and support from various parties is needed. Farmers' income also needs to be considered as an important factor that can support the involvement of the younger generation in the agricultural sector in order to overcome the challenges of aging farmers and the crisis of young farmers.